Cyber Arms: Security in Cyberspace. - Abaimov, Stanislav, 1989- author (CRC Press, 2020)
This book will raise awareness on emerging challenges of AIempowered cyber arms used in weapon systems and stockpiled in the global cyber arms race. Based on real life events, it provides a comprehensive analysis of cyber offensive and defensive landscape, analyses the cyber arms evolution from prank malicious codes into lethal weapons of mass destruction, reveals the scale of cyber offensive conflicts, explores cyber warfare mutation, warns about cyber arms race escalation and use of Artificial Intelligence (AI) for military purposes. It provides an expert insight into the current and future malicious and destructive use of the evolved cyber arms, AI and robotics, with emphasis on cyber threats to CBRNe and critical infrastructure. The book highlights international efforts in regulating the cyber environment, reviews the best practices of the leading cyber powers and their controversial approaches, recommends responsible state behaviour. It also proposes information security and cyber defence solutions and provides definitions for selected conflicting cyber terms. The disruptive potential of cyber tools merging with military weapons is examined from the technical point of view, as well as legal, ethical, and political perspectives.